Morphine-induced trafficking of a mu-opioid receptor interacting protein in rat locus coeruleus neurons - Jaremko, Kellie M. (2013)
Opiate addiction is a devastating health problem, with approximately 2 million people currently addicted to heroin or non-medical prescription opiates in the United States alone. In neurons, adaptations in cell signaling cascades develop following opioid actions at the mu opioid receptor (MOR). A novel putative target for intervention involves interacting proteins that may regulate trafficking of MOR. Morphine has been shown to induce a re-distribution of a MOR-interacting protein Wntless (WLS, a transport molecule necessary for secretion of neurotrophic Wnt proteins), from cytoplasmic to membrane compartments in rat striatal neurons. Given its opiate-sensitivity and its well-characterized molecular and cellular adaptations to morphine exposure, we investigated the anatomical distribution of WLS and MOR in the rat locus coeruleus (LC)-norepinephrine (NE) system. Dual immunofluorescence microscopy was used to test the hypothesis that WLS is localized to noradrenergic neurons of the LC and that WLS and MOR co-exist in common LC somatodendritic processes, providing an anatomical substrate for their putative interactions. We also hypothesized that morphine would influence WLS distribution in the LC. Rats received saline, morphine or the opiate agonist [D-Ala2, N-Me-Phe4, Gly-ol5]-enkephalin (DAMGO), and tissue sections through the LC were processed for immunogold-silver detection of WLS and MOR. Statistical analysis showed a significant re-distribution of WLS to the plasma membrane following morphine treatment in addition to an increase in the proximity of gold-silver labels for MOR and WLS. Following DAMGO treatment, MOR and WLS were predominantly localized within the cytoplasmic compartment when compared to morphine and control. In a separate cohort of rats, brains were obtained from saline-treated or heroin self-administering male rats for pulldown co-immunoprecipitation studies. Results showed an increased association of WLS and MOR following heroin exposure. As the LC-NE system is important for cognition as well as decisions underlying substance abuse, adaptations in WLS trafficking and expression may play a role in modulating MOR function in the LC and contribute to the negative sequelae of opiate exposure on executive function.